2010
DOI: 10.4276/030802210x12892992239431
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Using the Model of Human Occupation Screening Tool in a Joint Learning Disability Team

Abstract: ■ MOHOST enables consistent, evidence-based assessment without constraining professional autonomy. ■ MOHOST is straightforward and cost-effective and can be used with a broad range of learning disabilities in various settings. ■ MOHOST-based reports are an effective way coherently to summarise occupational therapy assessments, interventions and recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 8 publications
3
15
0
1
Order By: Relevance
“…In summary, research indicates that (a) the MOHOST is a valid indicator of factors that influence occupational participation across a range of service users, (b) subscale scores derived from the MOHOST are meaningful and valid, (c) therapists can use the MOHOST in a reliable and valid manner, and (d) the MOHOST subscales discriminate between service users at different functional levels and are adequately sensitive to detect change in service users (Kielhofner et al 2009, Pan et al 2011. Its use in mental health and related areas has been explored in recent years (Mitchell and Neish 2007, Hawes and Houlder 2010, Lee and Harris 2010.…”
Section: Methodsmentioning
confidence: 99%
“…In summary, research indicates that (a) the MOHOST is a valid indicator of factors that influence occupational participation across a range of service users, (b) subscale scores derived from the MOHOST are meaningful and valid, (c) therapists can use the MOHOST in a reliable and valid manner, and (d) the MOHOST subscales discriminate between service users at different functional levels and are adequately sensitive to detect change in service users (Kielhofner et al 2009, Pan et al 2011. Its use in mental health and related areas has been explored in recent years (Mitchell and Neish 2007, Hawes and Houlder 2010, Lee and Harris 2010.…”
Section: Methodsmentioning
confidence: 99%
“…This endeavour is advanced by the application of theories that ground their practice and the use standardized measures (MACIVER et al, 2016). In practice, however, the quest to identify reliable assessments and measures continues to present dilemmas for therapists (HAWES;HOULDER, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Returning to the key question of interest, the issue concerns use of the MOHOST-SOF as a standalone assessment versus the full MOHOST. The full MOHOST is clearly a clinically useful tool, and practitioners report it to be a relatively quick and easy to use assessment (Forsyth et al, 2011;Hawes and Houlder, 2010;Mitchell and Neish, 2007). This, however, comes at the cost of length of requirements for multiple observations.…”
Section: Discussionmentioning
confidence: 99%
“…The results were that the MOHOST demonstrated good construct validity, item separation reliability, and concurrent validity, and the authors concluded the MOHOST was suitable for research and clinical purposes. Other research has shown that therapists using the MOHOST report it to be useful, helpful when making decisions, supportive of occupation-focused thinking, and useful for structuring client-centred practice (Forsyth et al, 2011;Hawes and Houlder, 2010;Mitchell and Neish, 2007).…”
Section: Previous Research On the Mohostmentioning
confidence: 99%